Ethical standards and perceptions of CRM among millennial consumers. Issue 5 (10th July 2020) - Cosgrave, David; O'Dwyer, Michele
Abstract : Purpose: This study explores the millennial perceptions of cause-related marketing (CRM) in international markets through the lens of an ethical continuum. Literature gaps exist in our understanding of cause-related marketing, ethics and millennials in an international context, with few studies offering insights into successful CRM campaigns in developed vs developing countries. Previous studies have yielded differing responses based on culture, sociodemographic and consumer perceptions. Design/methodology/approach: An exploratory qualitative research method was adopted to build the theory necessary to address this research gap. Semi-structured interviews were conducted with a convenience sample of 155 undergraduate and postgraduate students representing 17 nationalities. Interviews were conducted in two regions (Ireland and United Arab Emirates) representing developed and developing markets. Findings: Discrepancies exist between millennial consumers when it comes to ethical self-reporting, perceptions of CRM initiatives, choice criteria of CRM offers and purchase intentions. Findings also suggest that there is a relationship between the religious and ethical beliefs of millennials in certain regions. Gender showed no significant differences in perceptions of CRM. Originality/value: This study examines millennial perceptions of CRM from multiple nationalities in developed vs developing markets. It introduces the ethical continuum in international CRM as a lens to examine perceptions of millennial consumers. The study identifies that millennials should not be treated as a homogenous group, suggesting different choice criteria of millennial consumers based on their ethical standards. It demonstrates emerging support for the role of religion in successful adoption of CRM.